2005
DOI: 10.1117/12.601733
|View full text |Cite
|
Sign up to set email alerts
|

BEOL process technology based on proximity electron lithography: demonstration of the via-chain yield comparable with ArF lithography

Abstract: Proximity electron lithography (PEL) using the ultra-thin tri-layer resist system has been successfully integrated in our dual-damascene Cu/low-k interconnects technology for the 90-nm node. Critical comparison between conventional ArF lithography and PEL as to the via-chain yield for test element groups (TEGs) including approximately 2.9 million via chains was performed to demonstrate its production feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To control pattern collapse, Koba et al [2] indicated and demonstrated that tri-layer resist process had a high applicability for device fabrication in BEOL. Nohdo et al [3] also indicated Proximity electron lithography (PEL) using the ultra-thin tri-layer resist system has been successfully integrated in our dual-damascene Cu/low-k interconnects technology for the 90-nm process. Matsuura et al [4] describes process optimisation of UV curing for ultra Low-k SiOC (ULK-SiOC, k = 2.65) and High stress silicon nitride (HS-SiN) liner.…”
Section: Introductionmentioning
confidence: 99%
“…To control pattern collapse, Koba et al [2] indicated and demonstrated that tri-layer resist process had a high applicability for device fabrication in BEOL. Nohdo et al [3] also indicated Proximity electron lithography (PEL) using the ultra-thin tri-layer resist system has been successfully integrated in our dual-damascene Cu/low-k interconnects technology for the 90-nm process. Matsuura et al [4] describes process optimisation of UV curing for ultra Low-k SiOC (ULK-SiOC, k = 2.65) and High stress silicon nitride (HS-SiN) liner.…”
Section: Introductionmentioning
confidence: 99%
“…To control pattern collapse, Koba et al 2) proposed and demonstrated that a trilayer resist process has high applicability in device fabrication. Nohdo et al 3) also demonstrated proximity electron lithography (PEL) using an ultrathin trilayer resist system, which has been success-fully integrated into a dual-damascene Cu/low-k interconnect technology for the 90 nm process. Matsuura et al 4) described the process optimization of curing for ultralow-k SiOC (k ¼ 2:65) and a high-stress silicon nitride (HS-SiN) liner.…”
Section: Introductionmentioning
confidence: 99%